Exploring the Longitudinal Relationship Between Short Sleep Duration, Temperament and Attention Deficit Hyperactivity Disorder Symptoms in a Biethnic Population of Children Aged Between 6 and 61 Months: A Born in Bradford Study. Issue 9 (July 2023) - Stott, Jonathan; Coleman, Elizabeth; Hamilton, Anna; Blackwell, Jane; Ball, Helen L.
Objective: Examine the association between sleep duration, temperament and symptoms of Attention Deficit Hyperactivity Disorder (ADHD) in a biethnic child-population from The Born in Bradford cohort. Method: Parent-report sleep duration categorized children as: early short, late short, consistently short or consistently normal sleepers between 6 and 36 months. Temperament was measured using the Infant Characteristics Questionnaire at 6 months. The Strengths and Difficulties Questionnaire assessed symptoms of ADHD at 37, 54, and 61 months. Results: Normal sleepers before 18 months had significantly fewer ADHD symptoms at 37 months compared with consistently short sleepers. Fussiness at 6 months was significantly positively associated with ADHD symptoms at 37 and 54 months; but does not appear to mediate the relationship between sleep duration and ADHD symptoms. Conclusion: Awareness of the relationship between short sleep duration and fussiness in infancy and later ADHD symptomatology may support earlier identification of arising difficulties in children.